Implementation of Cognitive Restructuring Techniques to Improve The Open Mindedness of Students of SMPN 3 Masjid Raya Banda Aceh - Rizka Shalsa Billa; Mashuri; Muslima (Barkah Publishing, 2025)
This study aims to determine the influence of cognitive restructuring techniques on increasing the open mindedness of students of SMPN 3 Mesjid Raya Banda Aceh. An open-mindedness attitude or openness to new ideas and views is very important for the cognitive and social development of students because it can affect their learning process and social interaction. To maintain this attitude, one of the efforts that can be made is with cognitive restructuring techniques, which is an approach that aims to improve students' open-mindedness behavior This research used an experimental method with a one-group pre-test post-test design. The population amounted to 22 students in grades VII and VIII, are taken by using the total sampling technique. Data collection instruments are in the form of questionnaires and documentation. Data analysis was conducted using a paired sample t-test with a significance level of 0.05 after meeting the test prerequisites. The results of the study showed an increase in the average score from pretest (47) to posttest (75), after cognitive reconstruction techniques were carried out, then based on statistical tests also showed a ttable > tcal value (8,090 > 0.602), so that Ha was accepted and Ho was rejected. This proves that cognitive restructuring techniques have a positive effect on increasing the open mindedness of SMPN 3 Mesjid Raya Banda Aceh students